Air-stable redox-active nanomagnets with lanthanide spins radical-bridged by a metal–metal bond - Fupin Liu (Nature Portfolio, 2019)
Dilanthanide complexes that possess radical bridges exhibit enhanced magnetic exchange coupling, affording molecular magnets with high blocking temperatures. Here, the authors explore a series of dilanthanide-encapsulated fullerenes where the radical bridge is taken to its limit and the role is played by a single unpaired electron.